Molecular effects of polystyrene nanoplastics on human neural stem cells. - Raquel Martin-Folgar; Mª Carmen González-Caballero; Mónica Torres-Ruiz; Ana I Cañas-Portilla; Mercedes de Alba González; Isabel Liste; Mónica Morales (PLoS ONE, 2024)
Nanoplastics (NPs) have been found in many ecological environments (aquatic, terrestrial, air). Currently, there is great concern about the exposition and impact on animal health, including humans, because of the effects of ingestion and accumulation of these nanomaterials (NMs) in aquatic organisms and their incorporation into the food chain. NPs´ mechanisms of action on humans are currently unknown. In this study, we evaluated the altered molecular mechanisms on human neural stem cell line (hNS1) after 4 days of exposure to 30 nm polystyrene (PS) NPs (0.5, 2.5 and 10 μg/mL). Our results showed that NPs can induce oxidative stress, cellular stress, DNA damage, alterations in inflammatory response, and apoptosis, which could lead to tissue damage and neurodevelopmental diseases.